TOXICITY TEST OF Eusideroxylon zwageri BARK EXTRACT ON KIDNEY HISTOPATHOLOGY GLOMERULAR HYPERTROPHY AND HYDROPIC DEGENERATION - Gusti Erysa Nur Tsaniya; I Wayan Arya Krishnawan Firdaus; Nurdiana Dewi; Juliyatin Putri Utami; Bambang Setiawan (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: Ironwood bark extract (Eusideroxylon zwageri) has antioxidant properties such as tannins, phenolics, flavonoids, saponins and alkonoids. Most compounds in the ironwood bark extract were phenolics (31.28 mg GAE/g), flavonoids (30.48 mg CE/g), and proanthocyanidins (183.30 mg PE/g). These can be used as alternative herbal medicines, but also has toxic effects, so a toxicity test is necessary. Toxicity tests can be seen through histopathological parameters based on glomerular hypertrophy and hydropic degeneration. Purpose: To determine the toxic effect of ironwood bark extract administration at doses of 1,250 mg/kg, 2,750 mg/kg, and 4,750 mg/kg orally on the kidneys of Wistar rats based on histopathological appearance of glomerular hypertrophy and hydropic degeneration. Methods: Pure experimental study with a posttest-only with control design, consisting of 4 groups with 3 treatment groups given ironwood bark extract at doses of 1,250 mg/kg, 2,750 mg/kg, and 4,750 mg/kg, and 1 control group was given distilled water 2x1 ml every 24 hours orally for 14 days. Results: In administration of ironwood bark extract at doses of 2,750 mg/kgBW and 4,750 mg/kgBW, glomerular diameter was found increased. The histopathological hydropic degeneration showed a score of 1 in all dose groups. The research data were analyzed using the One Way Anova and Kruskal Wallis tests. Both tests showed no significant differences between groups. Conclusion: There was no toxic effect of ironwood bark extract at doses of 1,250 mg/kg, 2,750 mg/kg, and 4,750 mg/kg on the kidneys of Wistar rats based on histopathological appearance of glomerular hypertrophy and hydropic degeneration.